Analysis e Marketing, Product Innovation, and Brand Image on Purchase Decisions Janji Jiwa Coffee in Surakarta - Diva Novitasari; Ida Aryati; Ratna Damayanti (Jurnal Mantik, 2021)
The purpose of this research to analyze the effect of either simultaneously or partial e marketing, product innovation, brand image on purchasing decisions for Janji Jiwa coffee in Surakarta. The type of descriptive quantitative research. The population is the buyer of Janji Jiwa coffee in Surakarta. The sample is 100 respondents. Data obtained from questionnaire with accidental sampling technique. The results of the F test prove that e marketing, product innovation, brand image have a simultaneous and significant effect on the purchase decision of Janji Jiwa coffee in Surakarta, where the value of Fcount>Ftable (60,552 > 2,699) and the significance of 0,000 < 0.05. The t test results prove that e marketing has a positive and significant effect on the decision to purchase Janji Jiwa coffee with tcount>ttable (4,842 > 1,985) with a significant value of 0,000 < 0.05. Product innovation has a positive and significant effect on the purchase decision of Janji Jiwa coffee with a value of tcount>ttable (5,219 > 1,985) with a significant value of 0,000 < 0.05. Brand Image does not affect the purchasing decision of Janji Jiwa coffee with tcount>ttable (-0.401 >01.985) with a significant value of 0.689 > 0.05.